ACCEPTANCE OF INTERFAITH VALUES: A CASE STUDY OF ISLAMIC RELIGIOUS EDUCATION IN NON-MUSLIM STUDENTS - Indriyani, Dian; Imron, Ali; Deni Wijayatiningsih, Testiana (The Islamic Education and Multiculturalism Foundation, 2022)
Abstract: This study aims to understand the meaning of the acceptance of interfaith values ​​in learning Islamic religious education for non-Muslim students at STKIP Muhammadiyah Manokwari. Instilling multicultural values, tolerance and pluralism as well as building the character of non-Muslim students. the paradigm of social constructivism used, with a qualitative approach, as well as the type of case study research used in this study. The results of the study showed that non-Muslim students already had good religious, honest (sidq) attitudes (jihad), discipline, consistency (istiqomah), and tolerance (tassamuh) after receiving Al-Islam and Kemuhammadiyahan learning which was integrated with values. Islamic values ​​and understanding of kemuhammadiyahan. Another acceptance is that they are enthusiastic and happy during learning and when doing assignments. Self-confidence in understanding Islamic teachings even though they are non-Muslims and mutual respect between one student and another.